ANALYSIS OF VILLAGE FINANCIAL PERFORMANCE WITH REVENUE RATIO IN PEMATANG SERAI VILLAGE, LANGKAT DISTRICT - Khamilah Siregar, Oktarini; Arnita, Vina (Proceeding International Seminar of Islamic Studies, 2023)
Village financial management is the goal of improving village financial conditions by providing a good signal to village financial users. The use of Village Finance that is right on target will optimize village revenue, including village original revenue. The researcher wants to analyze village financial ratios seen from village revenue analysis, namely the degree of decentralization, village financial dependency ratio, analysis of village revenue growth, PADesa efficiency ratio, PADesa Effectiveness Ratio in Pematang Serai Village, Tanjung Pura District, Langkat Regency Government. A research method with a quantitative description for assessing village financial performance with APBDesa realization report data from 2018 to 2021. The results obtained are village financial performance through a ratio approach with village revenue analysis that village revenue is still around more than 96% dominantly hoping for transfer revenue central government so that the village of Pematang Serai is very dependent on the central government and cannot be independent in the village of Pematang Serai. The need to increase the village's original revenue by planning and supervising the collection of village fees and taxes, the movement of village spending which has an impact on the development of new investments in the village of Pematang Serai such as BUMDES and MSME actors.